Ever and Annual Use of Prostate Cancer Screening in African American Men. (January 2017) - Halbert, Chanita Hughes; Gattoni-Celli, Sebastiano; Savage, Stephen; Prasad, Sandip M.; Kittles, Rick; Briggs, Vanessa; Delmoor, Ernestine; Rice, LaShanta J.; Jefferson, Melanie; Johnson, Jerry C.
Since prostate cancer continues to disproportionately affect African American men in terms of incidence, morbidity, and mortality, prostate-specific antigen (PSA) screening plays an important role in early detection, especially when men engage in informed decision making to accept or decline this test. The authors evaluated utilization of PSA testing among African American men based on factors that are important components of making informed decisions. Utilization of PSA testing was evaluated based on whether men had ever had PSA testing and PSA testing during the past year in a community-based sample of African American men ages 50 to 75 ( n = 132). Overall, 64% of men ( n = 85) reported that they had ever had a PSA test; the mean ( SD ) age for first use of PSA testing was 47.7 ( SD = 7.4). The likelihood of ever having a PSA test increased significantly with physician communication (odds ratio [OR] = 14.2; 95% confidence interval [CI] = 4.20, 48.10; p = .0001) and with having an annual household income that was greater than $20, 000 (OR = 9.80; 95% CI = 3.15, 30.51; p = .0001). The odds of ever having a PSA test were also decreased with each unit increase in future temporal orientation (OR = 0.66; 95% CI = 0.47, 0.93; p = .02). Of the men who had ever had PSA testing, 57% were screened during the past year. Only health insurance status had a significant independent association with having annual PSA testing (OR = 5.10; 95% CI = 1.67, 15.60; p = .004). Different factors were associated significantly with ever having PSA testing and annual testing among African American men. African American men may not be making an informed decision about prostate cancer screening.